Trademark Dispute of Starbucks in Indonesia: Is There A Legal Protection? - Agus Riswandi, Budi; Parmitasari, Indah; Khairandy, Ridwan; ., Karimatul Ummah; ., Abdan Syakura (KnE Social Sciences, 2023)
In Starbucks Corporation Trademark Dispute against PT Sumatera Tobacco Trading Company, PT Sumatera Tobacco Trading Company won because it had previously registered the same Starbucks trademark as a cigarette. The ruling was made by the Commercial Court of Central Jakarta Decision No. 51/Pdt.Sus/Tra. However, the Starbucks Corporation won at the cassation (third instance) level in the Supreme Court by Decision No. 836 K/Rev.Sus-HKI/2022 since the owner of the coffee trademark was classified as a well-known trademark. In the wake of this, it is essential to research and evaluate how the judges’ processes differ between the instances and how is the protection system of companies and trademarks that are well-known in Indonesia. This study is carried out through normative legal research, using statutory and conceptual approaches, and the secondary legal materials were collected through literature studies and qualitative descriptive analysis methods. Keywords: Trademark Dispute, Starbucks, Legal Protection for Well-Known Trademark